Functional Shifting From Agricultural Land Into Non-Agriculture - I Ketut Arnawa; Nenette Tolentino Columna; Dian Tariningsih (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2022)
The main problem in this research was the conversion of agricultural land into non-agricultural land in the regional spatial plan. The occurrence of agricultural land shifting involved the government, land owners, investors and the community. The aims of this research was to analyze factors, economic, social, land conditions and the government as the reason of the conversion of agricultural land into non-agriculture. The research was conducted in Denbantas Village, Tabanan Regency, Bali, with the consideration that the village was shifting the function of agricultural land. The research sample was determined by proportional random sampling with total 148 respondents. The data were analyzed quantitatively and qualitatively, the research results found that the dominant factors of agricultural land shifting were the need for housing, public ignorance of the land function, there was no land as an alternative to build a residence, and the government lacked socialization about land functions according to the regional spatial plan. The research on the causes of conversion of agricultural land into non-agricultural need to be conducted to anticipate land conversion did not occur sustainably